Social capital in enabling quality health care: The case of a telemedicine project in Nepal. Issue 5 (9th August 2018) - Sein, Maung Kyaw; Thapa, Devinder
Abstract: Information and Communication Technology (ICT) can play a crucial role in meeting multifaceted developmental challenges such as providing access to quality health care in developing countries. Initiatives such as telemedicine have been vital in bringing health care to marginalized groups in remote areas of such countries. While the implementation and effects of telemedicine projects have been studied in the literature, the actual mechanisms and conditions that facilitate the process have seldom been addressed. In this paper, we present an interpretive case study of a telemedicine project in a remote mountainous region of Nepal. Our findings indicate that it was the action of a group of focal actors who leveraged a supportive social capital that resulted in successfully bringing in quality health care to marginalized groups in these remote villages. Our findings reveal social capital as a facilitating condition through which ICT can play a crucial role in meeting developmental challenges such as quality health care.